2020
DOI: 10.1002/jnr.24688
|View full text |Cite
|
Sign up to set email alerts
|

Reelin activates the small GTPase TC10 and VAMP7 to promote neurite outgrowth and regeneration of dorsal root ganglia (DRG) neurons

Abstract: Axonal outgrowth is a fundamental process during the development of central (CNS) and peripheral (PNS) nervous system as well as in nerve regeneration and requires accurate axonal navigation and extension to the correct target. These events need proper coordination between membrane trafficking and cytoskeletal rearrangements and are under the control of the small GTPases of the Rho family, among other molecules. Reelin, a relevant protein for CNS development and synaptic function in the adult, is also present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Our previous work and that of others suggested an important role of VAMP7-dependent secretion in neuronal development (Alberts et al, 2003;Burgo et al, 2012Burgo et al, , 2013Colombo et al, 2014;Fuschini et al, 2018;Gupton and Gertler, 2010;Jausoro and Marzolo, 2021;Martinez-Arca et al, 2000. These results were based on mRNA silencing approaches and expression of the auto-inhibitory Longin domain in cultured neurons and NGF-treated PC12 cells.…”
Section: Role Of Vamp7-dependent Secretory Er-phagy In Neurite Growthmentioning
confidence: 83%
“…Our previous work and that of others suggested an important role of VAMP7-dependent secretion in neuronal development (Alberts et al, 2003;Burgo et al, 2012Burgo et al, , 2013Colombo et al, 2014;Fuschini et al, 2018;Gupton and Gertler, 2010;Jausoro and Marzolo, 2021;Martinez-Arca et al, 2000. These results were based on mRNA silencing approaches and expression of the auto-inhibitory Longin domain in cultured neurons and NGF-treated PC12 cells.…”
Section: Role Of Vamp7-dependent Secretory Er-phagy In Neurite Growthmentioning
confidence: 83%
“…71 It was suggested that Reelin can stimulate the regeneration of dorsal root ganglia following axotomy. 72 Of note, the injection of purified Reelin increases the regional density of the dendritic spine and hippocampal CA1 long‐term potentiation coincides with spatial learning and memory, showing Reelin activity on synaptic function and cognitive performance in rodents. 73 Therefore, it can be proposed that the reduction of astrocytes in the injured sites correlates with the promotion of neurogenesis, leading to a reduction of astrocyte recruitment into the injured sites.…”
Section: Discussionmentioning
confidence: 97%
“…Based on the great body of experiments, three‐dimensional biomaterials not only offer a supportive environment for the transplanted cells, but also is capable of reducing glial scar formation 71 . It was suggested that Reelin can stimulate the regeneration of dorsal root ganglia following axotomy 72 . Of note, the injection of purified Reelin increases the regional density of the dendritic spine and hippocampal CA1 long‐term potentiation coincides with spatial learning and memory, showing Reelin activity on synaptic function and cognitive performance in rodents 73 .…”
Section: Discussionmentioning
confidence: 99%
“…Vesicle exocytosis is required for growth cone membrane extensions by fusion of plasmalemmal precursor vesicles at the plasma membrane of growth cones and is closely tied to cytoskeletal dynamics ( Futerman and Banker, 1996 ; Hausott and Klimaschewski, 2016 ; Nozumi and Igarashi, 2018 ), and a balance of endocytosis and exocytosis is involved in growth cone guidance ( Tojima et al, 2014 ; Tojima and Kamiguchi, 2015 ). The axon guidance cue reelin controls fusion of VAMP7-positive vesicles in regenerating dorsal root ganglion neurons ( Jausoro and Marzolo, 2021 ). Furthermore, synaptic-like vesicles in the growth cone are required for pioneer axon navigation in zebrafish ( Nichols and Smith, 2019 ).…”
Section: Introductionmentioning
confidence: 99%